Nuclear-Targeting Delivery of CRISPRa System for Upregulation of β-Defensin against Virus Infection by Dexamethasone and Phenylalanine Dual-Modified Dendrimer - Mingxiang Zuo; Xiaoxia Li; Shuang Liu; Bin Chen; Du Cheng (Advances in Polymer Technology)
The dual-modified dendrimer containing dexamethasone (DET) and phenylalanine (Phe) was prepared to deliver plasmid DNA encoding dCas9 and single-guide RNA (sgRNA) for specific upregulation of β-defensin. DET and Phe moieties synergistically enhanced the transfection efficiency and reduced cytotoxicity of dendrimers. Combination of three sgRNAs targeting β-defensin gene demonstrated higher activation efficacy of β-defensin than any single sgRNA and combinations of any two sgRNAs, showing an efficient inhibition of virus infection and replication. The titer of vesicular stomatitis virus (VSV) in the cells treated with dCas9-sgRNA targeting β-defensin was reduced by about 100-fold compared to that of cells treated with dCas9-scramble sgRNA (dCas9-scr sgRNA). In vivo experiments demonstrated that the DET- and Phe-modified dendrimer effectively delivered plasmid DNA encoding dCas9 protein into the airway epithelium, inducing β-defensin expression. Delivery of the CRISPR activation system by a dendrimer modified with DET and Phe was a promising approach against viral disease.